Design of a Composite Type Three-phase AC Output Busbar - ZHANG Yu (Kongzhi Yu Xinxi Jishu)
High compactness, low stray inductance and high power density are required in electric locomotive converter wiring, while the traditional cable and single-layer conductive copper are often difficult to meet the requirements. Due to the drawbacks of traditional busbars, a new three-phase AC output bus structure was introduced, which electrostatically sprayed with epoxy resin powder and laminated with multiple polyester film. By taking the advantages of the laminated busbar, it effectively improve the power density and reduce the stray inductance, as well as conveniently install. The feasibility was verified by ANSYS software simulation, including stray inductance, temperature rise and current density of the inverter AC output bus.